Produção e percepção oral em l2: os processos de transferência do conhecimento grafo fônico-fonológico do português brasileiro (L1) para o inglês (L2) e o desempenho em listening (L2) - Márcia Zimmer; Hélio Radke Bittencourt (Cadernos de Estudos Lingüísticos, 2011)
This study aims to establish a connection between L2 speech production and perception by contrasting the findings garnered from English word and nonword naming tasks performed by 156 Brazilian students of English with their scores at the listening section of TOIEC (Test of English for International Communication). The production-perception relationship is approached in an original fashion in this investigation, since data gathered from L2 production in word and nonword naming tasks is compared to the participants’ performance in listening comprehension tasks of longer excerpts of native speech – rather than perceptual tests of phones or words only. First, we investigated the rate of use of nine grapho-phonic-phonological transfer processes among 156 adult Brazilian ESL students according to their level of proficiency during word and nonword naming sessions. The findings showed a steep and significant decrease in the rate of use of processes of transfer as the level during ESL word production as the participants’ level of proficiency increased. However, when reading nonwords, the students’ performance worsened a great deal, that is, the rate of use of most transfer processes increased regardless of the subjects’ levels of proficiency. Second, in order to assert whether there could be connections between the production results and L2 speech perception. We found inverse and significant correlations.